Stimulating Kinesthetic Abilities Through Obstacle Course Games - Sari, Indah Permata; Ardina, Mona; Daryati, Melia Eka; Wahyuni, Desvi (Journal of Early Childhood Development and Education, 2025)
Background of study: Kinesthetic skills are an important aspect of early childhood development, but at the Pembina Arga Makmur State Kindergarten, there are still children who have difficulty running, jumping, and throwing balls. Aims and scope of paper: The purpose of this study is to understand how obstacle course activities affect the kinaesthetic abilities of Arga Makmur Kindergarten students, ages 5 to 6. Methods: The research methodology utilized a two-group pretest-posttest experimental design and a quantitative method. Out of the 48 preschoolers in the population, 24 children made up the sample. They were split into two groups at random: the experimental group and the control group. An independent sample t-test was used to assess the data after it was gathered through tests and observation. Result: The analysis results indicated a significance value of 0.000 < 0.05, indicating a substantial disparity in gross motor abilities between children who took part in the obstacle course and those who did not. Conclusion: Obstacle course games have a positive effect on improving children's gross motor skills. Obstacle course games can be used for physical learning activities with obstacles to train early childhood skills.